THE EFFECT OF WORK ENVIRONMENT AND WORK RESPONSIBILITY ON EMPLOYEE PERFORMANCE AT DEMAK AGUNG MOSQUE - Khusni Mubarok; Suparmi Suparmi (Proceeding of The International Conference on Business and Economics, 2023)
This study took the object of the Great Mosque of Demak. This study aims to determine the effect of the work environment and work responsibilities on the performance of the employees of the Great Mosque of Demak. The purpose of this study was to determine the effect of the work environment and work responsibilities on the performance of the employees of the Great Mosque of Demak. In this study, the sampling technique used was the saturated sampling technique or the sampling technique where all members of the population were used as samples so that a sample of 40 respondents was obtained. The results of the study indicate that there is a positive and significant influence between the work environment on employee performance and there is a positive and significant influence between work responsibility and employee performance.